Late Quaternary barrier and fringing reef development of Bora Bora (Society Islands, south Pacific): First subsurface data from the Darwin‐type barrier‐reef system. Issue 6 (28th April 2016) - Gischler, Eberhard; Hudson, J. Harold; Humblet, Marc; Braga, Juan C.; Eisenhauer, Anton; Isaack, Anja; Anselmetti, Flavio S.; Camoin, Gilbert F.
Abstract: The universally known subsidence theory of Darwin, based on Bora Bora as a model, was developed without information from the subsurface. To evaluate the influence of environmental factors on reef development, two traverses with three cores, each on the barrier and the fringing reefs of Bora Bora, were drilled and 34 uranium‐series dates obtained and subsequently analysed. Sea‐level rise and, to a lesser degree, subsidence were crucial for Holocene reef development in that they have created accommodation space and controlled reef architecture. Antecedent topography played a role as well, because the Holocene barrier reef is located on a Pleistocene barrier reef forming a topographic high. The pedestal of the fringing reef was Pleistocene soil and basalt. Barrier and fringing reefs developed contemporaneously during the Holocene. The occurrence of five coralgal assemblages indicates an upcore increase in wave energy. Age–depth plots suggest that barrier and fringing reefs have prograded during the Holocene. The Holocene fringing reef is up to 20 m thick and comprises coralgal and microbial reef sections and abundant unconsolidated sediment. Fringing reef growth started 8780 ± 50 yrbp ; accretion rates average 5·65 m kyr −1 . The barrier reef consists of >30 m thick Holocene coralgal and microbial successions. Holocene barrier‐reef growth began 10 030 ± 50 yrbp and accretion rates average 6·15 m kyr −1 . The underlying Pleistocene reef formed 116 900 ± 1100 yrbp, i.e. during marine isotope stage 5e. Based on Pleistocene age, depth and coralgal palaeobathymetry, the subsidence rate of Bora Bora was estimated to be 0·05 to 0·14 m kyr −1 . In addition to subsidence, reef development on shorter timescales like in the late Pleistocene and Holocene has been driven by glacioeustatic sea‐level changes causing alternations of periods of flooding and subaerial exposure. Comparisons with other oceanic barrier‐reef systems in Tahiti and Mayotte exhibit more differences than similarities.